Design Of Low Phase Noise Very High Frequency (VHF) Low Band Voltage Controlled Oscillator (VCO) For Transceiver Application - Yeap, Kim Huat (2011)
There is little research in transceiver technology for Very High Frequency (VHF) low band nowadays because many communication systems today use higher frequency bands. However, low band is still required in specific fields, such as public safety due to its extensive and precise coverage. This thesis researches improvement in the phase noise of the low band Voltage Controlled Oscillator (VCO). As such, the back-to-back varactor, the linearizing inductor, and the low noise biasing network are introduced. Sensible placement of the bypass capacitor, choke, and ferrite bead as well as proper selection of parts have been studied and implemented.